2011
DOI: 10.1007/s12038-011-9064-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical stress on nuclear and mitochondrial DNA from healthy sections of colon and rectum of patients with colorectal cancer

Abstract: Surgical resection at any location in the body leads to stress response with cellular and subcellular change, leading to tissue damage. The intestine is extremely sensitive to surgical stress with consequent postoperative complications. It has been suggested that the increase of reactive oxygen species as subcellular changes plays an important role in this process. This article focuses on the effect of surgical stress on nuclear and mitochondrial DNA from healthy sections of colon and rectum of patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…ROS production is increased upon abdominal surgery 44,45 and increases epithelial permeability 46,47 . Increased intraoperative oxidative stress was also detected in blood samples upon open but not laparoscopic surgery 48 and surgical stress also induces mitochondrial and nuclear DNA 49 . However, in the present study we did not find clear signs of oxidative stress during POI.…”
Section: Discussionmentioning
confidence: 94%
“…ROS production is increased upon abdominal surgery 44,45 and increases epithelial permeability 46,47 . Increased intraoperative oxidative stress was also detected in blood samples upon open but not laparoscopic surgery 48 and surgical stress also induces mitochondrial and nuclear DNA 49 . However, in the present study we did not find clear signs of oxidative stress during POI.…”
Section: Discussionmentioning
confidence: 94%
“…23 However, these authors have summarized data for hepatic and extrahepatic metastatic sites without mentioning, whether LN were included in their study. According to the literature, the widely ranging frequency of mitochondrial genomic variation between several studies could be due to varying age compositions of the investigated populations, 39,40 surgical stress induced in possibly adherent normal colon tissue, 41 different epithelium-stroma ratios of the tumors, 42 varying proportions of tumors with advanced stages, 23,42,43 and by differences in the applied definitions and diagnostic panels. 23 Direct sequencing, which was applied in the current study, has a limited detection level, and interpretation of data might be complicated by heteroplasmy, 23 especially, if the portion of tumor DNA is less than 20% of analyzed DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover it has been suggested that oxidative stress stimulates the expression of endogenous mitochondrial DNA methyltransferases (DNMTs) responsible of epigenetic modifications able to regulate the mitochondrial transcription [ 22 ] and promotes the increase of 8-hydroxy-2′-deoxyguanosine (8-oxodG) both in the nuclear and in mtDNA genome [ 23 , 24 ]. Similarly in nuclear genome the increase of 8-oxodG in CpG nucleotide [ 25 ] seems to diminish the ability of DNA methyltransferases (DNMTs) to methylate the adjacent cytosine [ 26 ].…”
Section: New Evidence Supporting the Mitochondrial Theory Of Agingmentioning
confidence: 99%